Irradiation-Induced Deinococcus radiodurans Genome Fragmentation Triggers Transposition of a Single Resident Insertion Sequence - Pasternak, Cécile (Public Library of Science, 2010)
Stress-induced transposition is an attractive notion since it is potentially important in creating diversity to facilitate adaptation of the host to severe environmental conditions. One common major stress is radiation-induced DNA damage. Deinococcus radiodurans has an exceptional ability to withstand the lethal effects of DNA–damaging agents (ionizing radiation, UV light, and desiccation). High radiation levels result in genome fragmentation and reassembly in a process which generates significant amounts of single-stranded DNA. This capacity of D. radiodurans to withstand irradiation raises important questions concerning its response to radiation-induced mutagenic lesions. A recent study analyzed the mutational profile in the thyA gene following irradiation. The majority of thyA mutants resulted from transposition of one particular Insertion Sequence (IS), ISDra2, of the many different ISs in the D. radiodurans genome. ISDra2 is a member of a newly recognised class of ISs, the IS200/IS605 family of insertion sequences.